Labour Law and Industrial Relations: Toward Renewal? - Coutu, Michel; Dukes, Ruth; Murray, Gregor (Relations industrielles / Industrial Relations, 2023)
AbstractThis article explores paths for the renewal of the study of industrial relations and labour law. Through a comparative historical review of these two fields of study, it examines their common roots and legacies and a range of renewal initiatives. It is argued that both fields need to reappropriate core values: recognition of the fundamental inequality of the parties to the employment relationship; and recognition of the need to compensate for this inequality through collective processes. The seeds of this renewal are identified in both labour law and industrial relations. Their future lies in the emergence of an integrated field of study of work and employment and in the role and future of work as a vector of democracy.SummaryIndustrial relations and labour law both suffered a relative decline during the latter decades of the 20th and the early 21st centuries. Through a comparative historical review of the field of study, this article explores current and past efforts by scholars in industrial relations and labour law to examine their common legacies in order to transcend the overly narrow confines of their fields and identify avenues for renewal. Both industrial relations and labour law have long shared a common object of study—work and employment—and would benefit from more systematic integration of their findings. Such an integration will be explored by broadening both analytical perspectives. Neither jurists nor industrial relations specialists should confine their understanding of law to the formal rules within state law. They should instead turn to analysis of the “living law” through empirical studies of its nature and effectiveness. Industrial relations, whose focus is on the future of work and society, requires a more substantive engagement with the social sciences, while both fields need a normative project to advance citizenship at work and democracy. In line with Arthurs’ observations on labour law (2011), such renewal also requires an understanding of how both can be used to challenge hegemonic institutions and initiate alternative approaches.